Evaluation Of Participation In Recreational Exercise With Basic Psychological Needs And Happiness Parameters During The COVID-19 Pandemic Process - Nazlı Deniz Öz; Murat Erdoğdu (Selcuk University, 2021)
This cross-sectional study aimed to characterize the basic psychological needs of individuals participating in recreational exercises during coronavirus disease (COVID-19) and to evaluate their level of happiness. A total of 182 adults (26 ± 6.13 years; 50.5% male, 49.5 female) and individuals who attended private gyms during the pandemic process participated in the study. The demographic information form created by the researchers in the study, "Basic Psychological Needs in Exercise Scale" (Vlachopoulos and Mchailidou, 2006; Vlachopoulos et al., 2013) and "Oxford Happiness Scale-Short Form" (Hills and Argyle, 2002; Doğan and Çötok, 2011) were used. As a result of the study, while there was no difference in the basic psychological needs scale (BPNES) and its sub-dimensions in exercise according to gender, a significant difference was found in favor of male participants (t = -4.344; p lt;0.01) in the happiness scale. When evaluated according to age, no significant difference was observed in the happiness scale, while a significant difference was found in the sufficiency and autonomy sub-dimensions of the BPNES sub-dimensions in favor of 33 years and over compared to age 21 and below. As a result of this study, it has been revealed that autonomy and competence are the primary needs that motivate individuals to exercise during the pandemic period. It has been confirmed that especially adult groups attach greater importance to these needs. The importance of internal regulators in dealing with obstacles in the period when pandemic can be seen as an obstacle to participation in recreational exercise has been demonstrated.